2015
DOI: 10.1680/macr.14.00214
|View full text |Cite
|
Sign up to set email alerts
|

Use of copper slag and washed copper slag as sand in concrete: a state-of-the-art review

Abstract: This paper provides the gist of the systematic review undertaken, involving evaluation, analysis, repackaging and modelling of all the literature that could be sourced on the subject. Copper slag (CS) and washed copper slag (WCS), as to be expected, have essentially similar basic physical (although WCS is usually finer than CS) and chemical characteristics and therefore they can be treated as one material. In-depth analysis of 2192 test data sourced from the literature showed that, given all the basic material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Production of 1 t of copper produces about 3 t of copper slag and about 24.6 million tons of copper slag is generated from world copper production every year . The recycled copper slag can be used in concrete as a substitute for fine aggregate and it has been reported that the copper slag could reduce the amount of water mixing and improve the fluidity of the concrete, while the mixing of the copper slag aggregate promoted the bleeding of the fresh concrete due to the high density and glassy smooth surface of the copper slag . One of the ways to reduce the bleeding is increasing the powder content in concrete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of 1 t of copper produces about 3 t of copper slag and about 24.6 million tons of copper slag is generated from world copper production every year . The recycled copper slag can be used in concrete as a substitute for fine aggregate and it has been reported that the copper slag could reduce the amount of water mixing and improve the fluidity of the concrete, while the mixing of the copper slag aggregate promoted the bleeding of the fresh concrete due to the high density and glassy smooth surface of the copper slag . One of the ways to reduce the bleeding is increasing the powder content in concrete.…”
Section: Introductionmentioning
confidence: 99%
“…15 The recycled copper slag can be used in concrete as a substitute for fine aggregate 16 and it has been reported that the copper slag could reduce the amount of water mixing and improve the fluidity of the concrete, [17][18][19][20] while the mixing of the copper slag aggregate promoted the bleeding of the fresh concrete due to the high density and glassy smooth surface of the copper slag. 21,22 One of the ways to reduce the bleeding is increasing the powder content in concrete. So, the bleeding situation might be improved if the copper slag was applied to powder-rich concrete like self-compacting concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Slow air-cooling creates a hard and crystalline product while fast cooling in water produces amorphous, glassy granulates [1]. The utilization and disposal of this waste CS becomes a concern for environmental protection agencies and governments, as to obtain 1 ton of clear copper 2.2-3 million tons of CS are produced [1], with an annual worldwide production of copper recently reported to be approximately 35 million tonnes [2]. Due to the increasing problem, a number of studies showed many possibilities of how this material could Abstract Copper slag is a voluminous waste material obtained during the manufacturing of copper (matte smelting process).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20]31]) but most of these papers used superplasticizers to enhance workability of high strength concrete mixes; also in one paper [26] the slump was found to slightly increase with copper slag percentage but overall it remained very low despite the fairly high water/cement ratio (w/c = 0.48). No measured data of moduli of elasticity were found in the literature, except in a Japanese paper as reported by [2]. Finally, there is little information widely available on various durability aspects of concrete with copper-slag fine aggregate, with few exceptions [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al (2015) describe a feasibility study of their innovative technology of converting into lightweight manufactured sand, by using foamed concrete, the silt size fractions arising from quarry fines, a construction demolition crushing process and various industrial wastes. Lye et al (2015) provide the outcome of their state-of-the-art review of the use of copper slag (CS) and washed copper slag (WCS) with systematic analysis and evaluation of the massive data assembled, showing how CS/WCS as a component of sand can be used and, in so doing, make other recycled and secondary materials more acceptable for their use in concrete. The study by Su et al (2015) describes their development work undertaken to improve, through surface treatment, the bond between the used tyre rubber crumb fine aggregates and the cement matrix, which resulted in minimising strength losses of concrete.…”
mentioning
confidence: 99%